Migrating Minds: Theories and Practices of Cultural Cosmopolitanism. Edited by Didier Coste, Christina Kkona, and Nicoletta Pireddu - Serena Fusco (Iperstoria, 2023)
Review of Migrating Minds: Theories and Practices of Cultural Cosmopolitanism, edited by Didier Coste, Christina Kkona, and Nicoletta Pireddu.